Corporal Punishment, Maternal Warmth, and Child Adjustment: A Longitudinal Study in Eight Countries - Jennifer E. Lansford (2018)
Two key tasks facing parents across cultures are managing children's behaviors (and misbehaviors) and conveying love and affection. Previous research has found that corporal punishment generally is related to worse child adjustment, whereas parental warmth is related to better child adjustment. This study examined whether the association between corporal punishment and child adjustment problems (anxiety and aggression) is moderated by maternal warmth in a diverse set of countries that vary in a number of sociodemographic and psychological ways. Interviews were conducted with 7- to 10-year-old children (N = 1,196; 51% girls) and their mothers in 8 countries: China, Colombia, Italy, Jordan, Kenya, the Philippines, Thailand, and the United States. Follow-up interviews were conducted 1 and 2 years later. Corporal punishment was related to increases, and maternal warmth was related to decreases, in children's anxiety and aggression over time; however, these associations varied somewhat across groups. Maternal warmth moderated the effect of corporal punishment in some countries, with increases in anxiety over time for children whose mothers were high in both warmth and corporal punishment. The findings illustrate the overall association between corporal punishment and child anxiety and aggression as well as patterns specific to particular countries. Results suggest that clinicians across countries should advise parents against using corporal punishment, even in the context of parent-child relationships that are otherwise warm, and should assist parents in finding other ways to manage children's behaviors. © 2014 Copyright Taylor & Francis Group, LLC.